Development of wrist monitoring device to measure wrist range of motion - Fong, Jin Hiung; M. S., Idris (IOP Publishing, 2020)
Study of human motion has been paying attention. From manual goniometer which consists of moving arm and a protector to assess the range of motion had been developed into equipment with strain gauge, flex sensor and many more. In recent years, the advance of microelectromechanical systems (MEMS) has boosted the use of inertia measurement unit (IMU). MPU 6050 is one of the IMU used in this study to assess wrist range of motion. Algorithm using Arduino has developed to improve the accuracy. A Bluetooth module is used to communicate with smartphone. An android application is developed to display data on smartphone. The device is tested to validate the reliability of measuring wrist range of motion. First test is carried out to test for the stability of each axis at 300, 600 and 900. For roll axis (counter-clockwise) and pitch axis (counter-clockwise) shows fluctuation. The other axis show slightly fluctuation. When tested on human wrist, the device able to give error in the range of 10 – 50. The result from device is compared with manual goniometer performed by physiotherapist. Placement of device o back of hand may affect the result. Front spot, middle spot and end spot placement has been tested to see the relationship. From testing, middle spot and end spot show better result compare to front spot. In performing radial deviation and ulnar deviation, end spot show significant closer result. However, this placement restricts the movement of wrist. Middle spot give overall close result.